2017
DOI: 10.1111/echo.13715
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of the application of transthoracic echocardiography‐guided three‐dimensional printing for the assessment of structural heart disease

Abstract: Transthoracic echocardiography-guided three-dimensional printed model (TTE-guided 3DPM) provides essential information for preoperative evaluation and decision making for patients with SHDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Another 24 studies (11.3%) applied a mixture of modalities across included patients (CCT and CMR, n = 21; CCT and 3D TEE, n = 2; and CCT, CMR, and 3D TEE, n = 1), while 2 studies (<1%) merged data from several modalities; 4 papers (1.9%) did not provide information on the sources of images. Echocardiography-derived 3DPSPs were limited to the depiction of cardiac valves (n = 16), 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ventricular or atrial septal defects (n = 3), 26 , 35 , 36 the left atrial appendage (n = 3), 17 , 37 , 38 or fetal hearts (n = 1). 39 …”
Section: Resultsmentioning
confidence: 99%
“…Another 24 studies (11.3%) applied a mixture of modalities across included patients (CCT and CMR, n = 21; CCT and 3D TEE, n = 2; and CCT, CMR, and 3D TEE, n = 1), while 2 studies (<1%) merged data from several modalities; 4 papers (1.9%) did not provide information on the sources of images. Echocardiography-derived 3DPSPs were limited to the depiction of cardiac valves (n = 16), 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ventricular or atrial septal defects (n = 3), 26 , 35 , 36 the left atrial appendage (n = 3), 17 , 37 , 38 or fetal hearts (n = 1). 39 …”
Section: Resultsmentioning
confidence: 99%
“…printing-guided percutaneous transcatheter closure of secundum ASD with rim deficiency in six patients [10]. This was followed by a report by Zhu et al in patients with multiple secundum ASD [11] and finally by Velasco Forte et al in patients with superior sinus venosus ASD and partial anomalous pulmonary venous drainage [12]. The current study found through 3D printed heart models that the lower edge of the inferior sinus venosus ASD is composed of the entrance of the inferior vena cava and the inferior wall of the left atrium, which was almost in a plane, and its shape was similar to the 'T' glyph or 'funnel' structure.…”
Section: Discussionmentioning
confidence: 86%
“…Automation of these processes through dedicated software would significantly increase the potential usefulness of this method. In the literature there are examples where more sophisticated software is applied to prepare 3D models (Mimics 19.0, Materialise, Leuven, Belgium), which significantly reduces the model preparation time [26][27][28]. Unfortunately, license cost precludes everyday use of such software.…”
Section: Discussionmentioning
confidence: 99%